MIGRAINE COMMON TRIGGERING FACTORS, AND ITS IMPACT ON ACADEMIC PERFORMANCE AMONG NURSING STUDENTS (Journal of Medical & Health Sciences Review, 2025)
Background: Migraine is common chronic neurological disorder. students are often exposed to various triggers that may significantly affect their daily lives and academic performance. Various factors such as stress, sleep disturbance, certain foods and environmental changes act as triggers for migraine attacks. The aim of this study to determine the migraine triggering factors, its impact on academic performance among nursing students.Methodology: Nursing students of Liaquat College of Nursing (Female) Jamshoro participated in a cross-sectional study.  All participants provided written informed consent. A total 141 nursing students were selected using a convenient non-probability sampling technique. Data were collected through a questionnaire, which include sections on demographic characteristics, determinants of migraine, effects of migraine on academic performance, and common migraine triggers.Results: The study was conducted on a total sample of 141 participants, including 42 first-year, 35 second-year, 33 third-year, 31 fourth-year students. The study shows that 34.04% of students suffer from migraines, Common symptoms include light/noise sensitivity 80.14% and nausea 19.85%. It negatively affects academics, with 91.48% missing lectures, 29.78% unable to do daily tasks, and around 33% facing difficulty concentrating, especially during exams. Major triggers were sleep disturbance 53.90% and caffeine intake 48.80%. Overall, the study highlights strong link between migraine, academic performance, and lifestyle-related factors.Conclusion: Migraine significantly affected student’s academic performance and daily activities. Common symptoms included sensitivity to light, nose and nausea. Sleep disturbance and caffeine were major triggers. Many students missed lectures and had difficulty concentrating. Managing triggers can help reduce migraine impact.